Design of Leading Type Retaining Walls: Case Study in Perumnas IV Padang Bulan, Jayapura City - Alfian Adie Chandra; Helen Gianditha Wayangkau; Ahmad Gifary (GoAcademica Research & Publishing, 2023)
Jayapura City is one of the Papua Province’s capital cities with an increasing population. One of the areas in Jayapura City, especially Perumnas IV Padang Bulan, is surrounded by hills. Infrastructure development in the densely packed Perumnas IV Padang Bulan area and increasingly narrow land has forced the local community to build infrastructure under the foot of the hills. Infrastructure development under the foot of the mountains is very prone to landslides or soil movement. There is a retaining wall planned so that the movement of the soil is restrained by the retaining wall so that no landslides occur, which endanger the community in the Perumnas IV Padang Bulan area. From a survey of the Perumnas IV Padang Bulan area in the form of topographic data and cone penetration data (CPT), contour data and cone penetration results (CPT) data were obtained for QC and fs values, then soil type classification was carried out with empirical correlation approaches, then active earth pressure calculations were carried out and passive from Rankine’s theory. As well as planning a safe leaning type retaining wall. From the results of the planning that has been done, the plan obtained is a leaning type retaining wall with concrete material, the height of the retaining wall reaches 3.1 meters, and the width of the foundation is 2 meters. Safe against overturning, shearing, and soil-bearing capacity.